The Effect of Overexpressed DdRabS on Development, Cell Death, Vesicular Trafficking, and the Secretion of Lysosomal Glycosidase Enzymes - Azure Yarbrough; Katherine Maringer; Entsar J. Saheb; Sanaa Jawed; John Bush (Biology, 2018)
Rab GTPases are essential regulators of many cellular processes and play an important role in downstream signaling vital to proper cell function. We sought to elucidate the role of novel D. discoideum GTPase RabS. Cell lines over-expressing DdRabS and expressing DdRabS N137I (dominant negative (DN)) proteins were generated, and it was determined that DdRabS localized to endosomes, ER-Golgi membranes, and the contractile vacuole system. It appeared to function in vesicular trafficking, and the secretion of lysosomal enzymes. Interestingly, microscopic analysis of GFP-tagged DdRabS (DN) cells showed differential localization to lysosomes and endosomes compared to GFP-tagged DdRabS overexpressing cells. Both cell lines over-secreted lysosomal glycosidase enzymes, especially β-glucosidase. Furthermore, DdRabS overexpressing cells were defective in aggregation due to decreased cell–cell cohesion and sensitivity to cAMP, leading to abnormal chemotactic migration, the inability to complete development, and increased induced cell death. These data support a role for DdRabS in trafficking along the vesicular and biosynthetic pathways. We hypothesize that overexpression of DdRabS may interfere with GTP activation of related proteins essential for normal development resulting in a cascade of defects throughout these processes.